Casa ideale Pier Paolo Calzolari = Maison idéale = Ideal home - Calzolari, Pier Paolo 1943-; Da Costa, Valérie 1971-; Sardes, Guillaume de 1979-; Semin, Didier 1954-; Vacquier, Stéphane; Viliani, Andrea (Nouveau Musée National de Monaco, 2024)
Setting out from the manifesto written in 1968, Casa ideale explores the poetic reach of Pier Paolo Calzolari’s work: a programmatic text that was to become a vehicle for a series of ideas that endowed the artist’s practice with direction, clearly outlining his intentions and evoking a range of interpretative possibilities. Published on the occasion of the exhibition of the same name at the NMNM – Nouveau Musée National de Monaco, the volume offers a wide-ranging overview on his research, retracing the key moments of a career that touched on the mainstays of Arte Povera as well as those of conceptual art. Through reproductions of historic works and performances, a new series of unpublished drawings and a collection of texts commissioned especially for the occasion, the book provides a rare opportunity to discover the world of Pier Paolo Calzolari, known for his unconventional approaches to the various disciplines of the visual arts. By constructing a process of metaphysical abstraction, Calzolari puts together a plural work, capable of combining various formal languages and triggering a transition between the physical and the aesthetic dimensions
Impressum: This book is published on the occasion of the exhibition "Pier Paolo Calzolari - Casa Ideale", NMNM, Villa Paloma, 17.11.2023 - 07.04.2024
Keywords: Calzolari, Pier Paolo -- 1943-; Calzolari, Pier Paolo / Exhibitions; Domestic space in art / Exhibitions; Home in art / Exhibitions; Espace domestique dans l'art / Expositions; Foyer dans l'art / Expositions; Ausstellungskatalog -- Nouveau Musée National de Monaco -- 17.11.2023-07.04.2024 -- Monaco